p190 RhoGAP, the major RasGAP-associated protein, binds GTP directly. - Foster, R (1994)
In mitogenically stimulated cells, a specific complex forms between the Ras GTPase-activating protein (RasGAP) and the cellular protein p190. We have previously reported that p190 contains a carboxy-terminal domain that functions as a GAP for the Rho family GTPases. Thus, the RasGAP-p190 complex may serve to couple Ras- and Rho-mediated signalling pathways. In addition to its RhoGAP domain, p190 contains an amino-terminal domain that contains sequence motifs found in all known GTPases. Here, we report that p190 binds GTP and GDP through this conserved domain and that the structural requirements for binding are similar to those seen with other GTPases. While the purified protein is unable to hydrolyze GTP, we detect an activity in cell lysates that can promote GTP hydrolysis by p190. A mutated form of p190 that fails to bind nucleotide retains its RasGAP binding and RhoGAP activities, indicating that GTP binding by p190 is not required for these functions. The sequence of p190 in the GTP-binding domain, which shares structural features with both the Ras-like small GTPases and the larger G proteins, suggests that this protein defines a novel class of guanine nucleotide-binding proteins.